POTENSI HERBAL INDONESIA DALAM BIDANG BEDAH ANAK: PENDEKATAN BIOMEDIK MOLEKULER TERHADAP PENYEMBUHAN LUKA, INFLAMASI, DAN IMUNOMODULASI - Mashdarul Ma’arif; Riki Nova; Febianne Eldrian; Dhina Lydia Lestari; Khomeini Khomeini (Nusantara Hasana Journal, 2026)
Herbal-based complementary therapy approaches have recently gained attention in pediatric surgery due to their potential to support wound healing, reduce inflammation, decrease oxidative stress, and accelerate tissue regeneration. Indonesia possesses rich biodiversity of medicinal plants that have the potential to be developed as adjuvant therapies based on evidence-based medicine. This article aims to review the potential of Indonesian herbal medicine in the context of pediatric surgery through a molecular biomedical approach, focusing on wound healing, anti-inflammatory, antimicrobial, and immunomodulatory mechanisms. The method used in this study was a narrative literature review by searching scientific articles from PubMed, Scopus, ScienceDirect, and Google Scholar databases published between 2015 and 2025. The review findings indicate that several Indonesian herbs, including turmeric (Curcuma longa), moringa leaves (Moringa oleifera), ginger (Zingiber officinale), aloe vera (Aloe vera), and temulawak (Curcuma xanthorrhiza), exhibit biological activities through the regulation of NF-κB, TGF-β, VEGF, and PI3K/Akt pathways, as well as modulation of inflammatory cytokines and oxidative stress. The bioactive compounds of these herbs have the potential to accelerate angiogenesis, fibroblast proliferation, collagen synthesis, and wound epithelialization. Molecular approaches suggest that Indonesian herbal medicine has promising potential as a complementary therapy in pediatric surgical patients, particularly in the management of postoperative wounds and tissue inflammation.